The m6A demethylase FTO suppresses glioma proliferation by regulating the EREG/PI3K/Akt signaling pathway - Zhai, Yong; Li, Caili; Cao, Lihui; Zhang, Shen; Liu, Xiao; Ren, Junwei; Liu, Yue (Frontiers in Cell and Developmental Biology, 2025)
BackgroundGlioma, the most prevalent primary intracranial tumor, is characterized by aggressive proliferation and formidable treatment challenges. The N6-methyladenosine (m6A) demethylase, Fat mass and obesity-associated protein (FTO), is a critical regulator of gene expression, but its precise role in glioma remains controversial. This study aimed to elucidate the function and underlying molecular mechanisms of FTO in glioma progression.MethodsWe integrated bioinformatic analysis of 1,027 glioma patients from public cohorts (TCGA and CGGA) with a comprehensive experimental approach. In vitro studies in U251 and U87MG glioma cells involved gain- and loss-of-function assays to assess proliferation, colony formation, and cell cycle progression. Mechanistic investigations included Western blotting, qRT-PCR, and mRNA stability assays. An in vivo subcutaneous xenograft model was used to validate the tumor-suppressive role of FTO.ResultsOur analysis revealed that lower FTO expression is significantly associated with higher tumor grade and poorer overall survival in glioma patients. Functionally, FTO overexpression inhibited proliferation and induced G1 phase cell cycle arrest, whereas FTO knockdown enhanced these malignant phenotypes. Mechanistically, we identified Epiregulin (EREG) as a key downstream target of FTO. Loss of FTO increased global m6A levels and enhanced EREG mRNA stability, leading to its upregulation. This, in turn, activated the PI3K/Akt signaling pathway, evidenced by increased phosphorylation of PI3K and Akt and subsequent downregulation of p53 and p21. The in vivo model confirmed that FTO overexpression suppressed tumor growth, while its knockdown accelerated it.ConclusionOur findings establish FTO as a tumor suppressor in glioma. It inhibits proliferation by destabilizing EREG mRNA in an m6A-dependent manner, thereby inactivating the PI3K/Akt signaling cascade. These results highlight FTO as a potential prognostic biomarker and a promising therapeutic target for glioma.